Mobile colistin resistance: Prevalence, mechanisms, and current detection methods - Nguyen Quang Truong; Le Huyen Ai Thuy; Svetlana A Egorova; Lidiia A Kaftyreva; Hoang Quoc Cuong (Ho Chi Minh City Open University Journal of Science - Engineering and Technology, 2022)
Colistin is considered the last-line antibiotic against multidrug-resistant Gram-negative bacterial infections. The global dissemination of Mobile colistin resistance mcr-harboring bacteria is threatening public health. Such isolates have been detected in various reservoirs including animals, food products, the environment, and humans. From these reservoirs, the isolates are approximate: 53% from animals; 39% from humans; 5% from the environment; and 3% from food. Bacterial distributions were: E.coli 91%; Salmonella 7%; and Klebsiella 2%. Among the 10 mcr variants, mcr-1 and mcr-9 are the most prevalent (up to 95% and 64.53%, respectively, in different studies) while other variants account for 5%. The coexistence of mcr and other antibiotic resistance genes in single isolates is a significant concern; mcr variants carried by different plasmid types increase antibiotic resistance and transfer of mcr genes to other bacteria. The hypothesis that the food chain is intimately involved in mcr gene transfer is supported by the presence of mcr-harboring isolates in animals and foods relative to humans. Cheaper, quicker, and more effective diagnostic tools for detecting colistin-resistant bacterial phenotypes and genotypes are essential and urgent. Currently, high quality tests include RPNP (99.3% specificity, 96.7% sensitivity) and MRPNP (95.4% specificity, ~100% sensitivity). LBJMR, CHROM agar, COL-APSE, and Super Polymyxin are now the best media to screen the bacteria, with near 100% selectivity. Multiplex PCR is a suitable method to quickly and accurately detect mcr genes in E. coli and Salmonella . Multi-drug resistant Gram-negative bacteria remain a global burden and need to have continuous and effective surveillance.